ATU-01 Endoscopic ampullectomy: how safe is it in UK settings?. (June 2019) - Abdelrahim, Mohamed; Varytimiadis, Lazaros; Al-Kandari, Asma; Hossain, Ejaz; Goggin, Patrick; Bhandari, Pradeep; Arndtz, Sophie
Abstract : Introduction: Endoscopic ampullectomy is a minimally invasive technique of treating non-invasive lesions involving the ampulla of Vater, and offers an alternative to major surgical intervention. In this study, we describe the safety and outcome of this procedure from a large, tertiary centre. Methods: Data were prospectively collected on an electronic database. Parameters related to ampullectomy outcome and complications were retrospectively analyzed. Results: A total of 37 cases were included in this analysis, between 2009 and 2018. Average age was 66. Female represented 59.4% of patients. Mean duration of follow up was 62.3 weeks. 23 (62.1%) lesions were pure ampullary, and the remaining involved the duodenal wall as well. Lesions ranged from 5 to 80 mm in size, with average size of 21.58 mm. 5 patients (13.5%) had familial adenomatous polyposis FAP. Pre resection histology confirmed HGD in one patient (2.7%), and neuro-endocrine tumor NET in one case (2.7%). Post resection histology showed focal adenocarcinoma in 1 patient (2.7%). Prophylactic PD stenting was performed in 26 cases (70.2%), adjunctive APC used in 7 cases (18.9%), and Submucosal injection in 27 cases (72.9%). En-bloc resection was achieved in 16 (43.2%), while piecemeal in 21 cases (56.7%). Recurrence observed in 9/37 cases (24.3%). Piecemeal resection and lack of submucosal injection were significantly associated with higher risk of recurrence (P=0.0485, P=0.0471, respectively). Early bleeding (including intra-procedural and bleeding within 24 hours of procedure) happened in 5 patients (13.5%), delayed bleeding (after 24 hours) in 2 cases (5.4%), all were successfully treated endoscopically. Only 1 patient (2.7%) had Pancreatitis, and one patient developed ampullary stenosis post procedure. There was no report of perforation, need for emergency surgery or 30 day mortality in this series. Conclusion: Our series demonstrate the safety of this procedure in the UK setting. Piecemeal resection, and lack of submucosal injection seems to predict risk of recurrence, while size of the lesion did not significantly affect this outcome.